Representações sociais sobre as lesões de fluorose dentária por jovens acometidos residentes em área endêmica de São Francisco, Minas Gerais - Brasil. - Lia Silva de Castilho (2009)
Dental fluorosis caused by the consumption of fluoridated groundwater is endemic in some regions of Brazil. The solution involves securing water from appropriate alternative sources and an understanding of how the population perceives the relationship between disease andwater consumption. This study investigated beliefs and attitudes regarding the causes of fluorosis among the rural population of a municipality located in central Brazil. Over there, this paper describes the psychosocial consequences of this condition and how it hasaffected the self-esteem of adolescents and young people. Content analysis and social representation theory were employed in the discussion of the issues based on information gathered from semi-structured interviews. Interviews included 23 adolescents with fluorosis detected in a previous epidemiological survey, 14 teachers of these young people and 3 authority figures involved in the solution of the problem. For the organoleptic characteristics that it imposes on groundwater (salty flavor, whitish coloration and turbidity) and its association with negative aspects related to household use, calcareousrock is considered the cause of the blemished teeth. Even after contact with the researchers who investigated this phenomenon and participated in its solution, the population continues to resist accepting fluoride as the cause of the problem and does not fully agree with the useof water from other sources due to a lack of trust in its quality. Faulty perceptions regarding the causes of dental fluorosis and the difficulty in covering the water treatment costs compromise the implantation of uncontaminated surface water supply. The study revealed the affected individuals were embarrassed to smile at strangers due to a presumedassociation between fluorosis and a lack of dental hygiene. Further findings include conflicts between affected and non-affected students at school, problems in pursuing a romantic relationship and uncertainties regarding a professional future. Disbelief and scepticism were observed regarding the ethical position that science can offer a solution tothe problems stemming from the disease. Lesions from severe dental fluorosis appear to be a stigmatising factor and have contributed toward suffering and self-exclusion among an entire generation of adolescents and young people.